Human Impacts on Seals, Sea Lions, and Sea Otters: Integrating Archaeology and Ecology of the Northeast Pacific - Ray Pierotti (Ethnobiology Letters, 2013)
Review of Human Impacts on Seals, Sea Lions, and Sea Otters: Integrating Archaeology and Ecology of the Northeast Pacific. Todd J. Braje and Torben C. Rick, editors. 2011. University of California Press, Berkeley. Pp. 328. $65.00 (hardcover). ISBN 9780520267268.